Menu Close

f-R-R-g-R-R-f-xy-f-x-g-x-f-y-g-y-g-xy-f-x-g-y-f-y-g-x-d-fg-dx-




Question Number 818 by 123456 last updated on 17/Mar/15
f:R→R  g:R→R  f(xy)=f(x)g(x)+f(y)g(y)  g(xy)=f(x)g(y)+f(y)g(x)  ((d(fg))/dx)=?
f:RRg:RRf(xy)=f(x)g(x)+f(y)g(y)g(xy)=f(x)g(y)+f(y)g(x)d(fg)dx=?
Commented by prakash jain last updated on 17/Mar/15
x=1, y=1  f(1)=2f(1)g(1)  g(1)=2f(1)g(1)  f(1)=g(1)  f(1)=2[f(1)]^2   f(1)=0 ∨f(1)=(1/2)  If f(1)=0,  g(1)=f(1)=0, f(x)=g(x)=0  If f(1)=(1/2), g(1)=f(1)=(1/2)  g(x)=(1/2)[f(x)+g(x)]⇒f(x)=g(x)  f(x)=[f(x)]^2 +(1/4)  f(x)=g(x)=(1/2)
x=1,y=1f(1)=2f(1)g(1)g(1)=2f(1)g(1)f(1)=g(1)f(1)=2[f(1)]2f(1)=0f(1)=12Iff(1)=0,g(1)=f(1)=0,f(x)=g(x)=0Iff(1)=12,g(1)=f(1)=12g(x)=12[f(x)+g(x)]f(x)=g(x)f(x)=[f(x)]2+14f(x)=g(x)=12
Answered by prakash jain last updated on 17/Mar/15
Two solutions  f(x)=g(x)=0  f(x)=g(x)=(1/2)  ((d(fg))/dx)=0
Twosolutionsf(x)=g(x)=0f(x)=g(x)=12d(fg)dx=0

Leave a Reply

Your email address will not be published. Required fields are marked *